An assessment of measurement invariance in the 3- and 5-factor models of the Strengths and Difficulties Questionnaire: New insights from a longitudinal study. (1st December 2017) - DeVries, Jeffrey M.; Gebhardt, Markus; Voß, Stefan
Abstract: The Strengths and Difficulties Questionnaire (SDQ) is an internationally popular tool for assessing of psychological and psychosocial development; however, recent research has suggested it lacks measurement invariance in several situations. We expand on this discussion by examining the measurement variance of its two popular models across longitudinal measurements. We examined the fits of both models, conducted tests of invariance across time, and measured the change over time for each factor. We found that both models provide good fits and, furthermore, that strong measurement invariance was upheld across all measurement points for both models. Additionally, we found that problem scores increased and prosocial behavior scores decreased over time. We conclude that both models provide good fits of the data and have measurement invariance over time, but that more research is required regarding its measurement invariance across cultures. Highlights: Longitudinal validation of SDQ's psychometric properties Both standard 3 and 5 factor SEM models produced good fits. SEM modeled data supported strong invariance over time. Internalizing & externalizing behavior increased from ages 8–11.